"En Español Esa Palabra No Tiene Ningún Sentido:" A Cross-Case Analysis of Three Mexican American Dual Language Teachers' Language Ideologies and Instructional Differences. Issue 4 (2nd October 2018) - Briceño, Allison
ABSTRACT: This study profiles three Mexican American, dual language teachers in a qualitative cross-case analysis and asks (a) How do dual language teachers' linguistic backgrounds influence their language ideologies?; (b) How are language ideologies evidenced in teachers' instructional practices? Participants could be perceived as homogenous Mexican American women but had diverse linguistic backgrounds and ideologies. They include one native Spanish speaker born and educated in Mexico, one native Spanish speaker who was born in Mexico and attended high school in the United States, and one first-generation Mexican American teacher who was recovering Spanish as a heritage language. Interviews and classroom observations from a California school with a dual language strand were the primary sources of data. Findings show that the teachers' varied linguistic backgrounds influenced their language ideologies, and their language ideologies were apparent in distinct language development instructional practices. Teachers' surface-level homogeneity masked varied ideologies that influenced their instructional decisions in complex and sometimes problematic ways. Implications include the need for greater focus on language ideologies in teacher preparation and policy changes to support bilingual teacher development.